2008
DOI: 10.1097/bpo.0b013e31817762cb
|View full text |Cite
|
Sign up to set email alerts
|

Bone Stiffness in Children

Abstract: Although there are many publications concerning the mechanical behavior of adult bone, there are few data about mechanical properties of children's bone. In vivo bone stiffness measurement with Orthometer device has been validated and extensively used in adults to assess bone healing after fracture or lengthening. We hypothesized that in vivo stiffness measurement with Orthometer was applicable in children and was correlated with age, height, body weight, and corpulence index. The purpose was to establish base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This may have been the result of the introduction of the paracord, implant differences, and/or the inherent mechanical properties of skeletally immature bone as it has been shown that skeletally immature bone is inherently less stiff than adult bone. 9 Further investigation is needed to fully understand these differences.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been the result of the introduction of the paracord, implant differences, and/or the inherent mechanical properties of skeletally immature bone as it has been shown that skeletally immature bone is inherently less stiff than adult bone. 9 Further investigation is needed to fully understand these differences.…”
Section: Discussionmentioning
confidence: 99%